Prediction of Life Expectancy in Maluku Province Using Backpropagation Artificial Neural Networks - Yopi Andry Lesnussa; Francis Yunito Rumlawang; Endro Risamasu; Charlita Fhilya (Department of Matematics, Universitas Padjadjaran, 2020)
Life Expectancy at Birth (LE) is defined as the average estimated number of years a person can live to since their birth. The purpose of LE is to represent the health rate of a community. Backpropagation is an algorithm in artificial neural networks (ANN) used to predict or forecast data. This study aims to predict Life Expectancy in Moluccas. Based on the results of the analysis obtained an average forecasting success of 99.65% with the smallest error MAPE = 0,0035. Forecasting for the next 5 years shows that the Life Expectancy value tends to increase over the next 5 years from 2019-2023 at 65.7828 (2019) increasing to 66.6632 (2023).